IMPLEMENTASI HAKIM DALAM PENETAPAN HARTA GONO GINI AKIBAT ISBAT POLIGAMI DI PENGADILAN AGAMA KOTA MALANG - Mohamad Satria Negara; Ahmad Subekti; Moh Murtadho (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Polygamy is a marriage in which one party has more than one partner, or a husband who is married to more than one wife. Isbat polygamy is ratification or approval of marriage with a second, third, and later wife. Community property are all assets produced jointly by husband and wife since the marriage contract is held. The author uses qualitative methods that are examined in depth. To check the validity of the data, researchers used triangulation sources. In the decision of Malang City Religious Court Judges, the case is Number 1082 / Pdt.G / 2018 / PA.MLG. That the determination and distribution of community property can be decided if the applicant and the respondent have completed the requirements of the Court, and the Court has absolute conditions, namely filling in the information of the assets with the applicant and the respondent. Guidelines from the judges of the Malang City Religious Courts, namely the manual for the implementation of the duties and administration of religious courts The judge determines the determination and distribution of community property in polygamy permits by referring to the law, and the religious justice guidebook. More tightening the conditions for polygamy permits, so that there is a sense of respect for a woman, so that there is justice in the household.Key Word : Polygamy, Community Property, Isbat Polygamy.